Optical measurement of dimensional parameters of the breast with subjects in prone position - Rößler, Ann-Christin; Althoff, Felix; Jaeger, Florian; Kalender, Willi Alfred; Wenkel, Evelyn (Journal of Medical Imaging, 2015)
Various applications require information on breast parameters, such as breast length and volume. An optical system was designed and tested for measuring these parameters with subjects in a prone position. The study results were used for optimizing patient positioning and handling for a future breast computed tomography (BCT) system. Measurements were conducted using an optical measurement system. To test the functionality and accuracy of the system, measurements were performed using reference phantoms. Additionally, 20 women and 5 men were examined to calculate breast parameters in alternative positions and breathing states. The results of the optical measurements were compared with magnetic resonance imaging (MRI) measurements. Volume and length of the reference phantoms were determined with errors below 2%. The patient study demonstrated a mean breast volume of 530.7 ml for women during normal breathing. During an exhalation state, breast volume increased significantly by 17.7 ml in comparison with normal breathing. Differences with MRI measurements were found to be 3% for breast length and 9% for breast volume on average. The proposed optical measurement system was found to be suitable for measuring the dimensional parameters of the breast in a prone position and provides a tool for evaluating breast coverage for BCT.
EVALuna2:10117